Deciphering Surface-Localized Structure of Nanodiamonds - Li Ma; Zhijie He; Keyuan Chen; Hanqing Li; Yongzhi Wu; Jueyi Ye; Hongying Hou; Ju Rong; Xiaohua Yu (Nanomaterials)
Nanomaterials, heralded as the “new materials of the 21st century” for their remarkable physical and chemical properties and broad application potential, have attracted substantial attention in recent years. Among these materials, which challenge traditional physical boundaries, nanodiamonds (NDs) are widely applied across diverse industries due to their exceptional surface multifunctionality and chemical stability. Nevertheless, atomic-level manipulation of NDs presents considerable challenges, which require detailed structural analysis to thoroughly elucidate their properties. This study utilizes density functional theory (DFT), lattice dynamics, and molecular dynamics (MD) simulations to analyze the structural and property characteristics of NDs. Fine structural analysis reveals that, despite variations in particle size, surface layer thickness remains relatively constant at approximately 3 Å. DFT methods enable computation of the surface layer to capture subtle electronic characteristics, while the internal core is analyzed via MD. Further investigation into amorphous structure control indicates that ND surface amorphous structures with a packing coefficient above 0.38 are thermodynamically stable. This study offers a novel approach to nanomaterial control in practical applications by elucidating the core–shell interactions and surface structures of NDs.